Front Cover: Systematic Optimization of the iMALDI Workflow for the Robust and Straightforward Quantification of Signaling Proteins in Cancer Cells. Issue 5 (14th September 2020) - Froehlich, Bjoern C.; Popp, Robert; Sobsey, Constance A.; Ibrahim, Sahar; LeBlanc, Andre M.; Mohammed, Yassene; Aguilar‐Mahecha, Adriana; Poetz, Oliver; Chen, Michael X.; Spatz, Alan; Basik, Mark; Batist, Gerald; et al.
Abstract : Automated immuno‐MALDI workflow for the quantitation of protein biomarker concentrations in clinical samples. Automation protocols for each liquid handling step are presented, and the small footprint of the instruments required for this workflow are highlighted. This is reported by Bjoern C. Froehlich, Robert Popp, Constance A. Sobsey, Sahar Ibrahim, Andre M. LeBlanc, Yassene Mohammed, Adriana Aguilar Mahecha, Oliver Poetz, Michael X. Chen, Alan Spatz, Mark Basik, Gerald Batist, René P. Zahedi, and Christoph H. Borchers in article 2000034 .